Impact of pharmacological interventions on reproductive variables of prepubertal Bos indicus beef heifers - Alves, Rodrigo Lemos Olivieri Rodrigues (2025)
The objective of this PhD dissertation was to evaluate the physiological and reproductive variables of prepubertal prepubertal Bos indicus heifers raised under different feeding systems in response to pharmacological manipulations. The first chapter is a review addressing the physiological and endocrinological processes related to puberty and ovulation induction protocols applied in beef heifers, establishing the distinction between these two processes. The chapter compiles studies that employed pharmacological protocols prior to fixed-time artificial insemination (FTAI) protocols, based on the exogenous administration of progesterone (P4), with or without estradiol (E2), in Bos indicus s heifers aged 14 to 24 months, as well as Bos taurus heifers. The results demonstrated that the combination of P4 and E2 positively impacts uterine development, ovulation incidence, and fertility. Additionally, regardless of the pharmacological basis of the induction protocols, studies reported that beef heifers with a corpus luteum (CL) at the beginning of the FTAI protocol exhibited greater estrus expression and higher fertility. The second chapter presents an experiment involving 13-month-old prepubertal Nelore heifers raised on pasture-based feeding systems, subjected to one, two, or no ovulation induction protocols based on P4 and E2 prior to the FTAI protocol. Although both induction treatments resulted in a higher proportion of heifers with CL at the start of the FTAI protocol and greater estrus expression compared to the noninduction treatment, only heifers subjected to two protocols achieved higher pregnancy per AI (P/AI), particularly the lighter heifers. However, no effect on pregnancy loss was observed. Additionally, irrespective of treatment, age positively impacted fertility, whereas body weight did not influence the reproductive performance of the heifers. The third chapter encompasses an experiment conducted with 11-month-old prepubertal Nelore heifers raised in confinementbased feeding systems, subjected to two or no ovulation induction protocols based on P4 and E2 prior to the FTAI protocol. The results of this study indicated that heifers subjected to the induction protocols exhibited greater uterine development, a higher incidence of CL at the start of the FTAI protocol, and greater estrus expression, although no differences were detected in P/AI and pregnancy loss. Regardless of treatment, heifers that began the FTAI protocol with a CL achieved higher P/AI rates than those without a CL. Furthermore, weight and age positively influenced follicular diameter and uterine development; however, fertility was positively influenced only by body weight, particularly in younger heifers. This thesis concludes that pharmacological manipulations performed prior to the FTAI protocol in prepubertal heifers are highly effective in inducing ovulation but do not necessarily induce puberty. Additionally, the results are very influenced by farm-specific factors, particularly genetics and nutrition, highlighting the need to evaluate each production system to establish the most efficient reproductive strategies.